PENGETAHUAN DAN SIKAP SANTRI DENGAN KEPATUHAN PROTOKOL KESEHATAN COVID-19 DI PONDOK PESANTREN MADURA - Rahmad Wahyudi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Background: Compliance with health protocols is one of the concerns of the spread of covid-19. The boarding school environment is at risk of becoming a new cluster of covid-19 virus spread in Indonesia. Knowledge and attitudes become important in the implementation of the covid-19 health protocol. Objective: To know knowledge and attitudes with compliance with health protocols covid-19 in the environment of pondok pesantren madura. Method: This study uses the analytical descriptive design with a Cross sectional approach, with a sample number of 165 respondents using the simple random sampling technique, the instrument used is a questionnaire. Research results: Statistical test results with the the Spearman Rank statistical test p value = 0.000 < 0.05 then H0 was rejected and it was stated that there was a relationship The conclusion is that there is a relationship between the knowledge and attitudes of students towards compliance with the covid-19 Health protocol at the Al-Falah Sumber gayam Islamic boarding school.